"Chiefs do not talk law, most of them talk power." Traditional authorities in conflicts over land grabbing in Ghana*. Issue 3 (1st September 2020) - Kirst, Sarah
ABSTRACT: In the context of large-scale land deals in sub-Saharan Africa, social conflicts have increased. In many of these conflicts, traditional authorities are central actors. Whereas several studies highlight their significance as mediators in conflicts, their role as conflict actors is hardly considered. I address this lacuna by referring to a conflict around an agro-industrial project in Ghana. Using Steven Lukes' three-dimensional power approach I demonstrate how preexisting hierarchies between traditional authorities are reinforced. I argue that these hierarchies are mostly insignificant for everyday land use practices but become relevant in conflict settings, allowing traditional authorities to reinterpret existing social orders and institutional arrangements with the aim to achieve territorial control. An interplay of different forms of power simultaneously prevents broad opposition of land users against traditional authorities while, in this way, contributing to indirect legitimization of traditional authorities, the underpinning of their authority and deepening social division.